Influence of family functioning and resilience on psychological well-being among students at public high schools in Siak District, Riau, Indonesia - Desrianty, Mona (2022)
Nowadays, there is increasing interest in research focusing on psychological aspects of a person which play a major role in a person's life. In the educational context, student well-being is one of the main factors which influence his or her learning process. This study aims to examine the relationship between family functioning, resilience, and psychological well-being of students at a public high schools in Siak District, Indonesia. Besides, this research was to determine whether there is an influence as well as significant differences on family functioning and resilience towards the psychological well-being among male and female high schools students. In this study, a descriptive correlational study has been conducted which involves a total of 342 respondents. These respondents have been selected through cluster random sampling. The result shows that the students are found to have a medium level of family functioning, resilience, and psychological well-being. However, there is no difference in family functioning, resilience, and psychological well-being between male and female students. Besides, it is found that family functioning and resilience are significantly correlated with psychological well-being. This research only focuses on secondary schools students on 4 randomly selected schools in Siak District, Indonesia who are around 15 – 17 years old. So, it may not be suitable to be generalized for all secondary schools students in other provinces of Indonesia or nationwide. This study implies that for a student to successfully cope with any psychological problems, they need a functional family with affective involvement, good communication as well as the ability to regulate their behaviours properly. Schools with the support of the education office need to promote the psychological well-being of schools residents through sustainable programs, teacher leadership counselling guidance, and parental participation.